Chance and The Statistical Law of Large Numbers - D’Amico, Rosario (Journal of Mathematical Economics and Finance; Vol 7 No 2 (2021): JMEF, Volume VII, Issue 2(13), Winter 2021, 2021)
In this work we look at one special case to provide a rational basis for the following assertion known as Statistical Law of Large Numbers: If an event E has a constant probability p of occurrence on any one trial, and has occurred m times in n trials, then, if the relative frequency of E, m/n, approaches the value of a limit point l and the accuracy of the approximation increases as the number of trials increases, we have l = p. The argument we propose is based on the concepts of “event” and “trial”, formulated in a recent paper by the author himself, and their direct implications.